Changes in acetylcholine receptor expression : neuromuscular junction morphology and associated myonuclei in BALB/C mice following muscle contusion injury - Louw, Elizabeth Adrienne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.